The Influence of Tax Rates, Tax Knowledge, and Tax Sanctions on Tax Payment Compliance of Culinary MSMEs in South Lampung Regency - Tomy, Chairian; Nofitasari, Susi (Universitas Indonesia Mandiri, 2025)
This research was conducted to explain the effect of changes in tax rates, tax knowledge, and tax sanctions on tax payment compliance MSMEs. The population in this study is MSME actors in the culinary field who in Sleman Regency. The sampling technique is Simple Random Sampling with the calculation of the number of samples using the Slovin method. Total The sample in this study is 99 MSME actors. The results of this study show that tax knowledge and tax sanctions affect MSME tax payment compliance, Meanwhile, the tax rate has no effect on tax payment compliance MSMEs.